Midface Fractures II - Louis, Matthew; Agrawal, Nikhil; Truong, Tuan A. (Seminars in Plastic Surgery, 2017)
Facial fractures are a common source of emergency department consultations for the plastic surgeon. A working understanding of the evaluation, the assessment, the management, and the prevention of further injury when dealing with these fractures is vital. This second of a two-part series detailing the management of midfacial fractures serves as a guide for the appropriate workup and management of the wide variety of fracture patterns that are commonly encountered.
Keywords: midface fractures; LeFort fractures; dentoalveolar fractures; palatal fractures